Attraction, Entrance, and Passage Efficiency of Arctic Grayling, Trout, and Suckers at Denil Fishways in the Big Hole River Basin, Montana. Issue 4 (14th May 2022) - Triano, Ben; Kappenman, Kevin M.; McMahon, Thomas E.; Blank, Matt; Heim, Kurt C.; Parker, Albert E.; Zale, Alexander V.; Platt, Nolan; Plymesser, Katey
Abstract: The Big Hole River basin in southwestern Montana supports the only indigenous, self‐sustaining fluvial population of Arctic Grayling Thymallus arcticus in the conterminous United States, but the basin is fragmented by numerous low‐head irrigation diversion dams. Denil fishways at 63 diversion dams provide Arctic Grayling and other fishes opportunities for year‐round access to critical habitats; however, their efficiency has not been evaluated. We quantified attraction, entrance, and passage for hatchery‐reared Arctic Grayling, wild trout (Brook Trout Salvelinus fontinalis and Brown Trout Salmo trutta ), and wild suckers (White Sucker Catostomus commersonii and Longnose Sucker C. catostomus ) during 14 field trials conducted at six Denil fishways over a representative range of fishway slopes and hydraulic conditions using passive integrated transponder telemetry. Attraction (60.4–84.3%) and entrance (44.3–78.6%) efficiencies were variable across test conditions and reduced overall fishway efficiencies (19.1–55.8%). In contrast, upon entry, passage efficiencies were high (96.2–97.0%) for all taxa across all test conditions. Attraction of hatchery‐reared Arctic Grayling increased with upstream depth (a surrogate for fishway discharge) and attraction flow, but attraction of wild fish was less affected by these conditions. Entrance of Arctic Grayling, Brook Trout, and Brown Trout decreased with upstream depth and fishway slope, especially when plunging entrance conditions associated with shallow downstream depths were present. However, entrance of Arctic Grayling and both trout species increased with downstream depth, and submerged fishway entrances demonstrated promise for increasing entrance efficiency at fishways with high discharges and steep slopes. We demonstrate that comprehensive evaluations of fishway efficiency components can identify specific solutions that improve fishway efficiency; application of these engineering solutions at individual fishways (as needed) could improve their efficiency and further enhance aquatic connectivity for fishes in the Big Hole River basin and elsewhere.